Structural investigation on WlaRG from Campylobacter jejuni: A sugar aminotransferase. (9th February 2017) - Dow, Garrett T.; Gilbert, Michel; Thoden, James B.; Holden, Hazel M.
Abstract: Campylobacter jejuni is a Gram‐negative bacterium that represents a leading cause of human gastroenteritis worldwide. Of particular concern is the link between C. jejuni infections and the subsequent development of Guillain‐Barré syndrome, an acquired autoimmune disorder leading to paralysis. All Gram‐negative bacteria contain complex glycoconjugates anchored to their outer membranes, but in most strains of C. jejuni, this lipoglycan lacks the O‐antigen repeating units. Recent mass spectrometry analyses indicate that the C. jejuni 81116 (Penner serotype HS:6) lipoglycan contains two dideoxyhexosamine residues, and enzymological assay data show that this bacterial strain can synthesize both dTDP‐3‐acetamido‐3, 6‐dideoxy‐d ‐glucose and dTDP‐3‐acetamido‐3, 6‐dideoxy‐d ‐galactose. The focus of this investigation is on WlaRG from C. jejuni, which plays a key role in the production of these unusual sugars by functioning as a pyridoxal 5′‐phosphate dependent aminotransferase. Here, we describe the first three‐dimensional structures of the enzyme in various complexes determined to resolutions of 1.7 Å or higher. Of particular significance are the external aldimine structures of WlaRG solved in the presence of either dTDP‐3‐amino‐3, 6‐dideoxy‐d ‐galactose or dTDP‐3‐amino‐3, 6‐dideoxy‐d ‐glucose. These models highlight the manner in which WlaRG can accommodate sugars with differing stereochemistries about their C‐4′ carbon positions. In addition, we present a corrected structure of WbpE, a related sugar aminotransferase from Pseudomonas aeruginosa, solved to 1.3 Å resolution. Abstract : PDB Code(s):5U1Z ;5U20 ;5U21 ;5U23 ;5U24 ;3NYT